A methodological analysis of demolition works in Malaysia - Abdullah, Arham; Sohaili, Johan; Azman, Azizul; Kassim, Mohamad Adam (Faculty of Civil Engineering, 2008)
As Malaysia continues to progress towards achieving a developed status, shortage of land and space will require existing structures to be demolished, in order to make way for new development. The dilemma of insufficient land in urban areas to sustain growth and cater for increasing modernization demands will augment to a critical level. Therefore, there is dire need to expedite research in the field of demolition works within the country. This research was aimed at developing an overview as well as assessing the potential of demolition operations in Malaysia. Two varying methodologies were adopted comprising a case study and a questionnaire survey. The former looked into the Lumba Kuda Flats demolition operations which formed part of the Gerbang Selatan Bersepadu project. On the other hand, the latter targeted feedback from the local industry’s professionals.